2017
DOI: 10.1002/eej.22953
|View full text |Cite
|
Sign up to set email alerts
|

Unified Theory of Electromagnetic Induction and Magnetic Resonant Coupling

Abstract: SUMMARY The difference between electromagnetic induction and magnetic resonant coupling was pointed out in the first proposal of electromagnetic resonant coupling. However, there was no clear technical comparison between the two methods. Therefore, in this study, five circuits are compared by using a phasor diagram, which is a basic and well‐known method in electric circuit theory. The transition from typical electromagnetic induction to magnetic resonant coupling is shown. The mechanism of the high efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Usually, power transmission efficiency increases with coupling coefficient between coils. 19,20 Preliminary results of measuring relationship between coping coefficients for the coils shown in Figure 3 and efficiency showed that the efficiency was 80% at the coupling coefficient of .3 and 90% at .4. 17 Thus, in this paper, we set the coupling coefficient of .3 with an efficiency of 80% as a criterion for high-efficiency power supply.…”
Section: Coupling Coefficient Map and Evaluation Methodsmentioning
confidence: 98%
“…Usually, power transmission efficiency increases with coupling coefficient between coils. 19,20 Preliminary results of measuring relationship between coping coefficients for the coils shown in Figure 3 and efficiency showed that the efficiency was 80% at the coupling coefficient of .3 and 90% at .4. 17 Thus, in this paper, we set the coupling coefficient of .3 with an efficiency of 80% as a criterion for high-efficiency power supply.…”
Section: Coupling Coefficient Map and Evaluation Methodsmentioning
confidence: 98%
“…Here the same solenoid coils are used on both sides so that magnetic paths #12 and #34 occur in upper and lower parts, respectively, of the transfer coils as shown in Figure 6C. 7 With all windings separated, magnetic paths #1, #2, #3, #4 occur so that the share of paths #12 and #34 is reduced, and k c decreases. However, as windings #1 and #4, #2 and #3 grow apart, main flux declines, and k DAB decreases as well as k c .…”
Section: Implementation Of Proposed Methodsmentioning
confidence: 99%
“…2,3 However, inductive wireless power transfer (IPT) systems that can supply power without electric contact are extensively studied in terms of convenience and protection against electric shock from the charger's housing. [4][5][6][7][8][9] With nonresonant IPT, transmitted power and power factor in AC link heavily depend on the strength of magnetic coupling between primary and secondary windings. 7 In case of weak magnetic coupling, high voltage must be induced in the secondary winding in order to deliver power to a load, which means higher excitation current.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (18) includes the capacitor C 2 of the secondary coil. C 2 should be determined so as to maximize efficiency [17]. In other words, when Eq.…”
Section: Transformer Efficiency Optimal Loadmentioning
confidence: 99%